The Role of Institutional Factors Over the National Insurance Demand: Theoretical Approach and Econometric Estimations - Simona Laura DRAGOȘ; Cristian Mihai DRAGOȘ (Transylvanian Review of Administrative Sciences, 2013)
The insurance sector becomes a more and more important component for the national economic and financial development. Nevertheless, the consumption and the density, both for life and non-life insurances, reveal a great variation across countries. Academic literature treats frequently the importance of the economic and demographic factors. This study evaluates the determining institutional factors of the insurance demand using OLS Multiple Regressions models on a sample of 31 European countries. The econometric estimates, according to the theory, show that a country’s level of corruption is decisive for the development of the non-life insurances. For the life insurances, business freedom, fiscal freedom and government spending are the most relevant explanatory variables. The article emphasizes the mechanism through which the significant institutional factors influence the insurance density from a country.